2011
DOI: 10.1017/s0024282911000375
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relations of European shrubby taxa of the genusUsnea

Abstract: This study focuses on EuropeanUsneaspecies with sorediate shrubby thalli, with the aim to evaluate the morphological and chemical separation of species in the light of molecular data. Twenty-twoUsneaspecies, including widely distributed taxa such asU. diplotypus, U. fulvoreagens, U. glabrescens, U. lapponica, U. subfloridana, U. substerilisandU. wasmuthii, were included in the study using Bayesian and maximum parsimony analyses of nuclear ITS and beta-tubulin sequences. The analyses showed that: 1) most taxa t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 64 publications
(88 reference statements)
1
31
0
Order By: Relevance
“…The genus is recognized by a fruticose thallus with an elastic central cord in the medulla (Fig. 14) (Randlane et al 2009, Clerc 2011a, 2011b, Saag et al 2011). Much of the species taxonomy is poorly known due to the enormous morphological and chemical infraspecific variation.…”
Section: The Usneoid Cladementioning
confidence: 99%
“…The genus is recognized by a fruticose thallus with an elastic central cord in the medulla (Fig. 14) (Randlane et al 2009, Clerc 2011a, 2011b, Saag et al 2011). Much of the species taxonomy is poorly known due to the enormous morphological and chemical infraspecific variation.…”
Section: The Usneoid Cladementioning
confidence: 99%
“…S1). Finally, DB22671 fell at the base of a complex formed by U. fulvoreagens (Räsänen) Räsänen, U. glabrescens and U. pacificana, without support, close to a basal grade of specimens originally identified as U. diplotypus Vain., U. glabrescens and U. substerilis, all from Europe (Kelly et al 2011;Saag et al 2011), but relabeled U. pacificana (Mark et al 2016;Lücking et al 2020c). Phylogenetically, the Colombian sample would therefore be identified as U. aff.…”
Section: Querymentioning
confidence: 99%
“…In a detailed analysis of all available ITS barcoding data for this hyperdiverse genus (in the definition by Lücking et al 2017a), Lücking et al (2020c) demonstrated numerous shortcomings in sequence data pertaining to Usnea: first and foremost taxonomic and geographic gaps, but also substantial issues with sequence identifications and voucher information. In addition, species identification in Usnea is challenging, as many presumably widespread taxa represent complexes of partly unrelated lineages and much work remains to be done to fully resolve the taxonomy of this genus (Seymour et al 2007;Wirtz et al 2008Wirtz et al , 2012Lumbsch & Wirtz 2011;Saag et al 2011;Shen et al 2012;Truong & Clerc 2012Truong et al 2013a, b;Clerc 2016;Mark et al 2016;Gerlach et al 2017Gerlach et al , 2019Gerlach et al , 2020Clerc & Otte 2018;Grewe et al 2018;Lagostina et al 2018;Dorey et al 2019;Temu et al 2019;Lücking et al 2020c).…”
Section: Introductionmentioning
confidence: 99%
“…From these numbers, it is evident that recognizing species boundaries in lichenized fungi is still in a state of flux, and finding and applying the appropriate character sets and analytical tools appears to be one of the greatest challenges to empirical species delimitation (Crespo and Perez‐Ortega, 2009; Lumbsch and Leavitt, 2011). Parmeliaceae (Lecanorales), the largest family of lichen‐forming fungi with about 2700 species and 80 genera (Thell et al, 2012; Saag et al, 2013), has been an object of intensive phylogenetic studies during the last decade (e.g., Blanco et al, 2006; Crespo et al, 2007, 2010; Del‐Prado et al, 2010; Saag et al, 2011; Leavitt et al, 2013ac). The genus Vulpicida J.‐E.…”
Section: Currently Accepted Vulpicida Species Their Character Statesmentioning
confidence: 99%